ANALISIS TITIK PULANG POKOK USAHA KERIPIK PISANG GULA AREN PADA INDUSTRI “FLAMBOYAN” DI KELURAHAN PANAU KECAMATAN TAWAELI KOTA PALU - Nitha, Vella; Damayanti, Lien (AGROTEKBIS, 2018)
This research aims to know the revenue obtained in the business of banana chips Palm sugar industry Flamboyant period of 3 months in order this businesses reaches breakeven point, or in other words the venture suffered no loss or gain profit. The research was carried out on the industry's